THE DEVELOPMENT OF ENGLISH LEARNING MEDIA BASED ON ANDROID APPLICATION ON MATERIAL COMPLIMENTS TOWARD STUDENTS’ OF 10TH GRADE SENIOR HIGH SCHOOL - Herdina Utami; Prih Febtiningsih; Wandi Syahfutra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The purpose of this study was to develop English learning media based on an Android application for X SMA compliments material, as well as to determine the quality of media products. This study uses Research and Development (R&D) research and the model used is the ADDIE Development model which consists of 5 stages namely Analysis, Design, Development, Implementation and Evaluation. The data analysis technique used is feasibility and quality the media obtained with the instrument in the form of a questionnaire. This product has been validated by material experts, media experts. The results of the validation show that material experts obtain an average of 4.77 which is included in the